Effect of cadence selection on peak power and time of power production in elite BMX riders: A laboratory based study - Rylands, L. P.; Roberts, S. J.; Hurst, H. T.; Bentley, I. (Journal of Sports Sciences, 2017)
The aims of this study were to analyse the optimal cadence for peak power production and time to peak power in bicycle motocross (BMX) riders. Six male elite BMX riders volunteered for the study. Each rider completed 3 maximal sprints at a cadence of 80, 100, 120 and 140 revs · min-1 on a laboratory Schoberer Rad Messtechnik (SRM) cycle ergometer in isokinetic mode. The riders` mean values for peak power and time of power production in all 3 tests were recorded. The BMX riders produced peak power (1105 ± 139 W) at 100 revs/min with lower peak power produced at 80 revs/min (1060 ± 69 W, (F(2,15) = 3.162; P = .266; ny-Quadrat = 0.960), 120 revs/min (1077 ± 141 W, (F(2,15) = 4.348; P = .203; ny-Quadrat = 0.970) and 140 revs/min (1046 ± 175 W, (F(2,15) = 12.350; P = 0.077; ?2 = 0.989). The shortest time to power production was attained at 120 revs/min in 2.5 ± 1.07 s. Whilst a cadence of 80 revs/min (3.5 ± 0.8 s, (F(2,15) = 2.667; P = .284; ?2 = 0.800) 100 revs/min (3.00 ± 1.13 s, (F(2,15) = 24.832; P = .039; ?2 = 0.974) and 140 revs/min (3.50 ± 0.88 s, (F(2,15) = 44.167; P = .006; ny-Quadrat = 0.967)) all recorded a longer time to peak power production. The results indicate that the optimal cadence for producing peak power output and reducing the time to peak power output are attained at comparatively low cadences for sprint cycling events. These findings could potentially inform strength and conditioning training to maximise dynamic force production and enable coaches to select optimal gear ratios.